Nicotine on rat TRAM flap - Ely,Pedro Bins (2009)
PURPOSE: The transverse rectus abdominis myocutaneous (TRAM) flap is one of the preferential techniques used in breast reconstruction following mastectomy. Nicotine has a detrimental effect on cutaneous flap survival; although there are no experimental studies proving this effect on musculocutaneous flaps. The aim of this study is to verify the effect of nicotine on the rat TRAM flap. METHODS: 30 Wistar EPM-1 rats were randomly distributed in two groups: control and experimental. The animals of the control group received saline solution injected subcutaneously, in a volume of 0.2 ml, twice a day, during 28 days in the preoperative period. The animals of the experimental group were treated with nicotine, injected subcutaneously, in a dose of 2 mg/kg twice a day, during 28 days in the preoperative period. All the animals were submitted to the caudally based, right unipedicled TRAM flap. 48 hours after the procedure, a study of the viable area of the flap was done through photographic documentation. Statistical analysis was performed with nonparametric Mann-Whitney's test. RESULTS: The experimental group had significantly greater area of necrosis when compared with the control group (p<0.001). CONCLUSION: Nicotine increased the area of necrosis of the TRAM flap, in rats.